(untitled) (Proceedings of the YSU B: Chemical and Biological Sciences, 2001)
The influence of salt press upon sterile topinambur plants (Helianthus tuberosus L.) and its callus tissues was studied. In order to get salt-resistant cell lines and sterile plants, the concentration of NaCl in the nutrient medium was gradually augmented during the passages, which led to the the accumulation of one of the osmoprotectants – the free proline – under the influence of such treating. The proline synthesis was stimulated by low concentrations of NaCl (0.5% and 1%). The increase of NaCl concentration till 2% suppressed the growth of both the callus tissue and sterile plants. The addition of exogenous proline to the salt-containing medium has confirmed indirectly its role as a deference factor. The suppressing influence of the salt was decreased in the medium, containing both NaCl and proline. There was morphogenesis of the calli upon the regeneration media, though not of mass character. The regenerants received were grown and preserved by means of micrografting. Comparison with the literature data allows to conclude that there is a resemblance of cell mechanisms of salt-tolerance acquisition between cultivated in vitro cells and intact plants. The obtained salt-resistant callus lines and regenerant- plants of topinambur could serve as the base for subsequent selection of topinambur sorts, which will grow on the salines.